(untitled) (Innovation & Development in Engineering and Applied Science, 2022)
Psychological problems are present in health care workers in different areas, regardless of the place where they are located. The objective of this research is to represent the impact of psychosocial risk in health workers and how it affects their work performance. It is a methodological study that establishes criteria to identify in a descriptive and qualitative way the social problems that these workers are having. As a result of the impact of the pandemic (SARS-Cov-2) within health centers, strategies for the mitigation of these problems can be implemented, observing the presence of psychic and psychosocial risks of high prevalence that are common in health centers; they can contract an occupational clinical picture due to their work environment; among them are the emotional demands (EM), the hiding of emotions (EE), the sensory psychological demands (ES), among others. These risks mentioned above cause lack of concentration and performance when performing the assigned tasks, so that the health and safety of the worker must be prioritized to avoid problems within their social and family nucleus.